2019
DOI: 10.1155/2019/8659754
|View full text |Cite
|
Sign up to set email alerts
|

Tubal Origin of “Ovarian” Low-Grade Serous Carcinoma: A Gene Expression Profile Study

Abstract: Objective. Ovarian low-grade serous carcinomas are thought to evolve in a stepwise fashion from ovarian epithelial inclusions, serous cystadenomas, and serous borderline tumors. Our previous study with clinicopathological approach showed that the majority ovarian epithelial inclusions are derived from the fallopian tubal epithelia rather than from ovarian surface epithelia. This study was designed to gain further insight into the cellular origin of ovarian low-grade serous carcinomas by differential gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
10
0
3
Order By: Relevance
“…However, there has been controversy around the cells of origin of LGSC. Some investigators have suggested the fallopian tube as the origin of LGSC [ 14 , 16 , 17 ]. It is postulated that most epithelial inclusion glands are tubal in origin rather than ovarian due to invagination of the ovarian surface epithelium with metaplasia.…”
Section: Tumorigenesis/histogenesismentioning
confidence: 99%
“…However, there has been controversy around the cells of origin of LGSC. Some investigators have suggested the fallopian tube as the origin of LGSC [ 14 , 16 , 17 ]. It is postulated that most epithelial inclusion glands are tubal in origin rather than ovarian due to invagination of the ovarian surface epithelium with metaplasia.…”
Section: Tumorigenesis/histogenesismentioning
confidence: 99%
“…У свою чергу, тип ІІ, що відповідно має за аналог "high-grade" серозну карциному, характеризується високим рівнем генетичної нестабільності із 81 20/ Том XXV / 1 залученням мутації ТР53. Вірогідно мають місце й різні шляхи канцерогенезу цих двох типів серозних карцином яєчників [3,13,18].…”
Section: Results Group Immunophenotypes Showed Uniformity In the Expunclassified
“…85 20/ Том XXV / 1 Епітеліальні пухлини видалених фаллопієвих труб гістологічно були серозними тубулярними інтраепітеліальними карциномами (in situ) або "high-grade" серозними інвазивними карциномами. І головне, вони мали ідентичні до "highgrade" серозної карциноми яєчників мутацію ТР53, аберантну експресію протеїну р53, високу проліферативну активність та значну геномну нестабільність [5,10,18].…”
Section: метастатична перитонеальна серозна карцинома без відомого пеunclassified
See 1 more Smart Citation
“…In contrast to HGSCs, it was assumed that, LGSCs arose from ovarian epithelial inclusions, serous cystadenoma or adenofibroma, and then progressed to serous borderline tumors and invasive carcinoma [9][10][11][12][13]. However, a few recent studies explored some histomorphological changes in the FEs of fallopian tubes, and concluded that secretory cells in fallopian tubes could be the source of LGSCs [14][15][16].…”
Section: Introductionmentioning
confidence: 99%